Room‐temperature synthesis of a new stable (N2H4)WO3 compound: a route for hydrazine trapping. Issue 2 (13th March 2019) - Giovannelli, F.; Mathieu, C.; Fritsch, K.; Adil, K.; Goutenoire, F.; Habicht, K.; Delorme, F.
Abstract : A new (N2 H4 )WO3 compound has been obtained by mixing WO3 and aqueous hydrazine solution at room temperature for 24 h. The material crystallizes in the trigonal space group P 32 21 and is stable up to 220°C, greatly beyond the boiling point of N2 H4 (114°C). Abstract : A new (N2 H4 )WO3 compound has been obtained by mixing WO3 and aqueous hydrazine solution at room temperature for 24 h. The reaction is catalyzed by the presence of lithium. X‐ray, synchrotron and neutron diffraction techniques have shown that the material crystallizes in trigonal space group P 32 21 (No. 154). Chains of distorted WO4 tetrahedra extend along the a axis of the unit cell, linked by a corner‐sharing oxygen atom: the N2 H4 are in the voids between them. The thermal characterization shows that this new compound is stable up to 220°C, greatly beyond the boiling point of N2 H4 (114°C); thus making it a promising candidate for catalysis or trapping applications.